2021
DOI: 10.1002/gps.5626
|View full text |Cite
|
Sign up to set email alerts
|

How can urban environments support dementia risk reduction? A qualitative study

Abstract: Objective: Interventions to reduce the risk of cognitive decline and dementia largely focus on individual-level strategies. To maximize risk reduction, it is also necessary to consider the environment. With the majority of older people living in cities, we explored how urban environments could support risk reduction. Materials and Methods: In our qualitative study, we conducted semi-structured interviews with community members aged ≥65 years and stakeholders, all living in Leipzig, Germany. Interview guides we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…After this threshold, although the barriers increased the probability of having difficulties, the distinction between being assisted and coping with difficulties without assistance was not significant. Unlike other studies, we did not observe any significant associations with environmental barriers such as the presence of hills and slopes [ 17 ] or the absence/presence of public toilets [ 76 ]. Finally, regarding the immediate environment, using stairs/steps to get out lowered the probability of having no OADL restrictions, as found in several studies [ 12 , 14 ], with increasing pressure with the number of FLs.…”
Section: Discussioncontrasting
confidence: 99%
“…After this threshold, although the barriers increased the probability of having difficulties, the distinction between being assisted and coping with difficulties without assistance was not significant. Unlike other studies, we did not observe any significant associations with environmental barriers such as the presence of hills and slopes [ 17 ] or the absence/presence of public toilets [ 76 ]. Finally, regarding the immediate environment, using stairs/steps to get out lowered the probability of having no OADL restrictions, as found in several studies [ 12 , 14 ], with increasing pressure with the number of FLs.…”
Section: Discussioncontrasting
confidence: 99%
“…[9][10][11][12] Notably, despite being explicitly focused on individual-level behaviour change, these studies identified some key motivators and barriers that were beyond an individual's control, such as social acceptability (of smoking), 9 workplace and family support, 9 and social disengagement. 12 To our knowledge, only one study 13 has sought explicitly to identify views on population-level dementia risk reduction. Rohr et al…”
Section: Introductionmentioning
confidence: 99%
“…Röhr and colleagues from the Global Brain Health Institute have proposed a survey methodology with urban stakeholders. 4 This survey methodology could be used more widely across society so that policy changes might tend towards the cocreation (with stakeholders) of living and working spaces that are safer, more widely accessible, and are physically, mentally, and socially stimulating.…”
mentioning
confidence: 99%